Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2001
DOI: 10.1152/ajpheart.2001.280.3.h969
|View full text |Cite
|
Sign up to set email alerts
|

Impact of heart failure and exercise capacity on sympathetic response to handgrip exercise

Abstract: Peak oxygen uptake (VO(2 peak)) in patients with heart failure (HF) is inversely related to muscle sympathetic nerve activity (MSNA) at rest. We hypothesized that the MSNA response to handgrip exercise is augmented in HF patients and is greatest in those with low VO(2 peak). We studied 14 HF patients and 10 age-matched normal subjects during isometric [30% of maximal voluntary contraction (MVC)] and isotonic (10%, 30%, and 50% MVC) handgrip exercise that was followed by 2 min of posthandgrip ischemia (PHGI). M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
123
1
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 113 publications
(135 citation statements)
references
References 33 publications
(63 reference statements)
10
123
1
1
Order By: Relevance
“…Furthermore, these changes occurred progressively over time. As in human heart failure, [12][13][14][15] it is feasible that these alterations in EPR activity correlate well with the development of exercise intolerance. If so, this model may prove useful in determining the chronology of pharmacological and molecular modifications to the EPR (in relation to ventricular function) that mediate reductions in exercise capacity using techniques presently not available to human experimentation.…”
Section: Clinical Relevancementioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, these changes occurred progressively over time. As in human heart failure, [12][13][14][15] it is feasible that these alterations in EPR activity correlate well with the development of exercise intolerance. If so, this model may prove useful in determining the chronology of pharmacological and molecular modifications to the EPR (in relation to ventricular function) that mediate reductions in exercise capacity using techniques presently not available to human experimentation.…”
Section: Clinical Relevancementioning
confidence: 99%
“…[1][2][3][4][5][6] In addition, cardiovascular regulation during physical activity is clearly altered with CHF, because studies using dynamic and static forms of exercise have demonstrated augmentations in sympathetic nerve activity, vascular resistance, heart rate (HR), and blood pressure. [7][8][9][10][11][12][13][14][15] Two distinct neural control mechanisms are activated by exercise: central command and the exercise pressor reflex (EPR). Central command is a mechanism whereby signals from a central site responsible for recruiting motor units activate cardiovascular control areas in the brain stem.…”
mentioning
confidence: 99%
“…Previous work from our laboratory (13) has focused on the efferent sympathoneural limb of this somatic pressor reflex. When the afferent nerve endings in skeletal muscle that are responsive to metabolic products of work (metaboreceptors, primarily type IV fibres) [14]) are stimulated by isometric or isotonic exercise, the reflex increase in MSNA is elicited at a lower workload in HF CLINICAL STUDIES ©2008 Pulsus Group Inc. All rights reserved KKA Witte, CF Notarius, J Ivanov, JS Floras.…”
mentioning
confidence: 99%
“…Augmentation of this relationship in HF patients is consistent with the concept that enhanced mechanoreceptor reflex activity exaggerates their ventilatory response to exercise. patients, and its magnitude is augmented (13). This sympathoexcitatory response is sustained when ischemic metabolites generated by exercise are trapped locally following post-handgrip ischemia by a proximal blood pressure cuff inflated to suprasystolic levels.…”
mentioning
confidence: 99%
“…This may help to ease some of the barriers to exercise, and increase patient adherence. This form of exercise has been found to result similar reduction in resting arterial blood pressure as that of conventional aerobic therapy, (6) and have beneficial effects, on autonomic nervous system regulation of blood pressure, (7) in improving cerebral haemodynamics (8) and forearm vascular response. (9) In spite of the above fact, very few studies have been conducted to evaluate the effect of IHG training on cardiovascular system, especially on cardiac morphology & functioning.…”
Section: Introductionmentioning
confidence: 90%